Entre irregularidades e sociabilidades: histórias de crianças e adolescentes pobres em Toledo/PR (1980-1990) - Neri, Cristiano (2012)
This work has the objective of discussing experienced stories of poor children and adolescents, taking as base judicial records of the Child, Youth and Family Court, in Toledo/PR County, inedited sources in the Brazilian historiography in the period between the 1980s and 1990s, guided by the Juvenile Code of 1979. These stories were outlined at the national level, when there was FUNABEM and therefore FEBEM, which dictated policy and legal changes for children in the country, in those years of civilian dictatorship military, established after 1964. In the far west region of Paraná, it was being built the Itaipu Hydroelectric Plant, which attracted itinerant workers and dispersed populations. In this period there also were processed technological changes in agriculture, forcing the rural exodus. These factors allowed regional cities, such as Toledo, to receive a significant increase in population. In the local and regional context, this process was marked by an intense movement of p oor migrants and itinerants, from many regions of the country, changing its social landscape. In Toledo, it was created the so-called "illegal neighborhoods," among other social problems. In the court documents, it was possible to realize a greater movement of poor children and adolescents, who started to occupy the city center or to conduct unlawful and illegal activities, receiving great social mobilization, all of this reported by the press. The analysis of judicial intervention in the lives of poor chil dren and adolescents, regarding the written process of the children, revealed the existence of safety nets, standardization, control, support and assistance. Many of them were articulated by religious institutions which supported by the regulation and social control through the work appreciation. In some cases, children and adolescents circulated among the family and the street, the police and other institutions created by the state to deal with the "irregular situations". The analysis of the experiences and practices of these individuals revealed a popular culture intending authoritarian norms forged in the period. These tensions were perceived, in this research, through a set of tactics incorporated in the daily experience of urban life chocking with value s shaped by local dynamics and national political assumptions. The socialization of poor children and adolescents was processed in the movement between institutions and sociabilities which, within the lived possibilities, were active and participatory in the process.